2004
DOI: 10.1002/bin.166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prior access and environmental enrichment on stereotypy

Abstract: A young boy's stereotypy was first evaluated in two daily 30 min sessions (one in the morning and one in the afternoon) during a free operant (FO) condition. Results from the two daily sessions during FO showed that stereotypy was lower during the second session of the day, suggesting that prior access had affected later engagement in stereotypy. The effects of environmental enrichment (EE) with music, EE music plus a guitar, and EE music plus a guitar plus contingent music loss on stereotypy were also evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
40
2
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 14 publications
4
40
2
2
Order By: Relevance
“…Interestingly, each participant displayed high levels of what was arguably a more salient form of stereotypy during TV (with visual and audio) than during No TV (low ambient stimulation). This finding is consistent with previous studies (Carter et al, 2004;Rapp, 2004;Van Camp et al, 2000) and is potentially important because it suggests that merely enriching the environment with preferred stimulation may produce undesirable effects on automatically reinforced behavior. Specifically, the The highest probability stereotypy prior to the TO body rock phase.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, each participant displayed high levels of what was arguably a more salient form of stereotypy during TV (with visual and audio) than during No TV (low ambient stimulation). This finding is consistent with previous studies (Carter et al, 2004;Rapp, 2004;Van Camp et al, 2000) and is potentially important because it suggests that merely enriching the environment with preferred stimulation may produce undesirable effects on automatically reinforced behavior. Specifically, the The highest probability stereotypy prior to the TO body rock phase.…”
Section: Discussionsupporting
confidence: 93%
“…Although a recent review by Rapp and Vollmer (in press) concluded that most forms of stereotypy are automatically reinforced, little is known about specific antecedent events that may influence automatically reinforced behavior. In fact, the antecedent event that most often associated with stereotypy is 'low environmental stimulation' with and without reference to social and tangible reinforcers (e.g., Berkson & Davenport, 1962;Berkson & Mason, 1963, 1964Emerson, Hatton, Robertson, Henderson, & Cooper, 1999;Hall, Thorns, & Oliver, 2003;Horner, 1980;Iwata, Dorsey, Slifer, Bauman, & Richman, 1982/1994.A handful of studies have shown that the presence of a particular, often preferred, stimulus sets the occasion for some individuals to engage in automatically reinforced problem behavior (Carter, Devlin, Doggett, Harber, & Barr, 2004;Friman, 2000 Rapp, 2004;Van Camp et al, 2000). Friman demonstrated that a young child engaged in thumb sucking only when he held a small cloth.…”
mentioning
confidence: 98%
“…When presession noninteraction has been provided in previous research (e.g., Rapp, 2004), it acted as an AO, which we replicated with 2 participants (range=5%-38% decrease). For the other 2 participants, we found that the presession noninteraction condition acted as an EO (range = 4.4%-19.7% increase).…”
Section: Discussionmentioning
confidence: 95%
“…Wehmeyer (1995) points out those stereotypical behaviors are complex and complete eradication is not a reasonable expectation. Strategies have been developed to reduce stereotypical behaviors, including consequence-based interventions such as response cost (Falcomata, Roane, Hovanetz & Kettering, 2004;Rapp, 2004), reinforcing an alternative behavior (Lovaas et al, 1987;Rehfeldt & Chambers, 2003), differential reinforcement of other behaviors (Rapp, 2007;Ringdahl et al, 2002;Taylor, Hoch, & Weissman, 2005), response interruption (Ahearn, Clark, MacDonald, & Chung, 2007), noncontingent access to a matched sensory stimulus (Higbee, Chang, & Endicott, 2005), and conditioning items or activities as reinforcers (Nuzzolo-Gomez, Leonard, Ortiz, Rivera, & Greer, 2002). However, to be effective, intervention procedures should be matched to the variables (social and non-social) that maintain stereotypy, as identified by a functional behavioral assessment (FBA) or functional analysis (FA; Hanley, Iwata, & McCord, 2003).…”
mentioning
confidence: 99%